MATERNAL MORTALITY IS A KEY INDICATOR OF THE HEALTH SYSTEM - B. Sh. To‘rayev; S.H. Samatova (Web of Journals Publishing, 2025)
The health status of any given country depends upon maternal and infant mortality rates, which play a crucial role in evaluating the country’s population health, quality of care, socioeconomic status, and poverty.
Keywords: Maternal mortality, Near-miss, Asia-Pacific, maternal death, maternal morbidity.